Small-area variations in overweight and obesity in an urban area of Nigeria: The role of fast food outlets - Osayomi, Tolulope; Orhiere, Maryanne A. (Bulletin of Geography. Socio-economic Series, 2017)
Overweight and obesity are two related health issues of epidemic proportions. In Nigeria, these health conditions have been emerging only recently. The extant literature shows inter-city variations in the prevalence of overweight and obesity in Nigeria. However, they say little about intra-city variations of these health problems in Nigerian urban centres. Thus, the focus of the study was to determine the small-area variations in the prevalence of overweight and obesity in an urban area of Nigeria and its association with socio-economic, environmental, dietary and lifestyle risk factors. With the aid of a questionnaire, information on the demographic, socio-economic, lifestyle, household and neighbourhood characteristics of respondents was obtained from respondents. Overweight and obesity were computed based on the self-reported height and weight of respondents, using the Body Mass Index (BMI) formula. A simple linear regression model was estimated to determine the individual and collective effects of risk factors. Findings showed that there were noticeable spatial variations in the prevalence of overweight and obesity which result from the varying contextual and compositional characteristics among the political wards of the Ibadan North LGA. Physical proximity to fast food outlets was the only significant factor driving the spatial pattern of obesity (b=0.645; R2=0.416). The paper suggests that government and health officials should formulate area-specific obesity prevention and control plans to curb this growing epidemic in Nigeria.